2017
DOI: 10.14382/epitoanyag-jsbcm.2017.16
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of alumino-silicates functionalized titanium as potential adsorbent: An industrial possibility

Abstract: nowadays different industrial sectors are highly contributing towards the discharge of heavy metal in various environmental compartments and it is one of the foremost environmental concerns due to their high toxicity and destructive impacts impact on human health. the effluents discharge from paint and leather industries usually contain considerable amount of lead and mercury which ultimately accumulates along the food chain and causes severe damage to the nervous system. various conventional methods have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Deformation behavior of porous brittle media, in particular, ceramics, geological materials, etc., is currently studied in detail primarily for ceramic with unimodal pore-size distribution (unimodal porosity), made by the method of partial sintering [1][2][3][4][5][6][7]. At the same time, it has been shown that threshold values of the pore-space volume exist for such materials at which both the deformation and subsequent fracture modes change substantially.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deformation behavior of porous brittle media, in particular, ceramics, geological materials, etc., is currently studied in detail primarily for ceramic with unimodal pore-size distribution (unimodal porosity), made by the method of partial sintering [1][2][3][4][5][6][7]. At the same time, it has been shown that threshold values of the pore-space volume exist for such materials at which both the deformation and subsequent fracture modes change substantially.…”
Section: Introductionmentioning
confidence: 99%
“…The latter contribute to accumulation and movement of local volumes of the material into the pore space in addition to a portion describing linear elastic strain seen at low stresses. Such deformation behavior is called pseudo-plastic because of the shape of the stress-strain curve similar to plastic metallic and elastic polymeric materials [5,6,8]. Moreover, it has been shown that the character of deformation depends on the mean pore size as well [5,6,9].…”
Section: Introductionmentioning
confidence: 99%
“…The specific surface area is a dominant parameter for zeolites [4]. Obtain the necessary magnitude of specific surfaces of materials depends not only on their chemical and mineralogical composition, but also on physical, mechanical and rheological parameters of the used materials [5,6]. It is known that mechanical processing in activator mills can change the structure, specific surface area, crystal composition of zeolite containing materials and occasionally improve their processing properties [7].…”
Section: Introductionmentioning
confidence: 99%